A FIRST RECORD OF THE ALIEN MANTIS SPECIES HIERODULA TENUIDENTATA (MANTODEA: MANTIDAE) IN SERBIA (Acta Entomologica Serbica, 2021)
An alien mantis species, Hierodula tenuidentata, has expanded its areal in Europe in the last few years. It was registered in several European countries, including some on the Balkan Peninsula. Herein are presented for the first time records of H. tenuidentata on the territory of Serbia, several from the capital city of Belgrade, and one from Novi Kneževac, a town in the northern part of country. The species was recognized for the first time in photos posted in a Facebook group of insect lovers and enthusiasts in 2019, but positive identification only took place in 2020 after group members collected specimens. Social networks can be a very important tool for the monitoring of invasive species in general, and invasive mantids in particular, especially due to their size and attractiveness.